Ruin probability of insurer in a discrete time setting with heavy-tailed insurance and financial risks - Seah, Xin Hui (2019)
This paper investigates the probability of ruin within a finite period of time in the context of an insurance company. It examines the reserve of an insurance business that is currently invested in a risky asset. There are 2 types of risks faced by the insurer: financial and insurance risks. This paper assumes that the risks have heavy-tailed distribution so as to mirror the real world, and aims to find estimates of the finite time ruin probability when insurance risk dominates financial risk and also when financial risk dominates insurance risk.